A Design of Framework for Smart Services of robots in Intelligent Environment - Kim, Joo-Hyung; Kim, Dong-Won; You, Bum-Jae; Park, Gwi-Tae (International Journal of Control and Automation, 2019)
This paper presents a framework for smart services of robots in an intelligent environment. Within such intelligent environment, the target platform consists of service robots and a framework for smart services including task allocation and task scheduling. For task allocation, we use an auction-based method and a knapsack problem algorithm. In this paper, the characteristics of the algorithm for allocation balancing are to delegate executing task to another robot, to reallocate the delayed task to more than one robot, and to withdraw overallocated robots from the current task.